Personality Theories : Development, Growth, and Diversity. - Allen, Bem P. (Taylor and Francis, 2005)
Examines the major movements in the field of personality through a historic and humanistic approach. THis book provides a comprehensive introduction to key personality theorists by combining their biographical information with their contributions to the field and their ranking among the world's most respected psychologists.